Regenerative Medicine Using Nanotechnology: A Review - Patel, Dipen (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTRegenerative medicine is considered to have the potential for developing new treatments for previously untreatable, or difficult to treat, diseases. Regenerative medicine is an emerging multidisciplinary field that aims to restore, maintain or enhance tissues and hence organ functions. Regeneration of tissues can be achieved by the combination of living cells, which will provide biological functionality, and materials, which act as scaffolds to support cell proliferation. Mammalian cells behave in vivo in response to the biological signals they receive from the surrounding environment, which is structured by nanometer-scaled components. Therefore, materials used in repairing the human body have to reproduce the correct signals that guide the cells towards a desirable behavior. Nanotechnology is not only an excellent tool to produce material structures that mimic the biological ones but also holds the promise of providing efficient delivery systems. The application of nanotechnology to regenerative medicine is a wide issue and this short review will only focus on aspects of nanotechnology relevant to biomaterials science. Specifically, the fabrication of materials, such as nanoparticles and scaffolds for tissue engineering, and the nanopatterning of surfaces aimed at eliciting specific biological responses from the host tissue will be addressed.